Spatial models cannot compensate for sampling designs unstructured relative to isotopic variation: implications for baseline isoscape development in the Mediterranean Sea - Sarah Magozzi; Clive N. Trueman; Matthew R.D. Cobain; Kirsteen M. MacKenzie; Katie St. John Glew; José A. Canseco; Eric Díaz-Delgado; Emanuela Fanelli; Paola Rumolo; Joan E. Cartes; Boris Espinasse; Davide Agnetta; et al. (Progress in Oceanography, 2026)

Plasma Metal Concentration is Sex Dependent and Associated with Fragility Fractures: Results of METOSTEO Cohort - François Robin; Alexandre Mercier-Guery; Simon Cadiou; Alexia Leloix; Marie-Laure Island; Olivia Berthoud; Martine Ropert; Olivier Loréal; Pascal Guggenbuhl (Biological Trace Element Research, 2026)

Vacuum in-tube extraction (V-ITEX): A tutorial review of theoretical principles, operational parameters, and applications - Lucie K. Tintrop; Simon Wacker; Florian Kopiec; Stefan Cretnik; Pascal Fuchsmann (Analytica Chimica Acta, 2026)

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Mechanical properties of Inuvik-Tuktoyaktuk highway built on permafrost over the years of operation from 2019 to 2024 - Farshad Kamran; Jean-Pascal Bilodeau; Eileen Catalina Castilla Duarte; Simon Dumais; Guy Doré (Cold Regions Science and Technology, 2026)

Sensitivity and Specificity of the Poststroke Spasticity Monitoring Questionnaire (PSMQ) for Remote Monitoring of Spasticity Development: Interim Analysis From an Ongoing Epidemiology Study - Richard D. Zorowitz; Laura Serrano Barrenechea; Simon Butet; David Hernández Herrero; Rama Prasad; Pascal Lecomte; Sophie Vandenbremt; Simon Page; Mathieu Beneteau; Pascal Maisonobe; Alessandro Picelli (Toxicon, 2026)

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Massive increase of intertidal seagrass coverage in a large estuarine system revealed by four decades of Landsat imagery - Carlos A.S. Araújo; Simon Bélanger; Pascal Bernatchez; Mathieu Cusson (Remote Sensing Applications: Society and Environment, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Optimising sub-metre resolution 3D geomorphic change detection over large areas using multitemporal airborne laser scanning with Sentinel-1 InSAR and Sentinel-2 optical observations - Simon J. Walker; Scott N. Wilkinson; Tim R. McVicar; Pascal Castellazzi; Sana Khan (Remote Sensing of Environment, 2025)

Effects of wind turbine dimensions on the collision risk of raptors: A simulation approach based on flight height distributions - Tonio Schaub; Raymond H.G. Klaassen; Caroline De Zutter; Pascal Albert; Olivier Bedotti; Jean-Luc Bourrioux; Ralph Buij; Joël Chadœuf; Celia Grande; Hubertus Illner; Jérôme Isambert; Kjell Janssens; et al. (Science of The Total Environment, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Major and trace elements behaviour in three weathering profiles developed on syenitic rocks in Ina pluton (syenitic set of Linté, Central Cameroon) - Yvan Demonstel Ntomb; Louise Marie Ngo Bidjeck Bondje; Eugène Pascal Binam Mandeng; Jacques Wassouo Wadjou; François Ndong Bidzang; Simon Ngos III (Journal of African Earth Sciences, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

X-ray tomography applied to tsunami deposits: Optimized image processing and quantitative analysis of particle size, particle shape, and sedimentary fabric in 3D - Saptarshee Mitra; Raphaël Paris; Laurent Bernard; Rémi Abbal; Pascal Charrier; Simon Falvard; Pedro Costa; César Andrade (Marine Geology, 2024)

Patient Perspectives on the Conduct of a Head-to-Head Study Comparing AbobotulinumtoxinAWith OnabotulinumtoxinA for Upper Limb Spasticity - Alberto Esquenazi; Ziyad Ayyoub; Monica Verduzco-Gutierrez; Pascal Maisonobe; Simon Page; Atul T. Patel (Toxicon, 2024)

Impact of Patient Input on the Study Execution of a Prospective, Epidemiological Study Assessing the Proportion of Stroke Survivors Who Develop Problematic Post-Stroke Spasticity - Richard D. Zorowitz; Laura Serrano Barrenechea; Simon Butet; Sergiu Groppa; David Hernández Herrero; Rama Prasad; Susan Sandars; Simon Page; Pascal Maisonobe; Alessandro Picelli (Toxicon, 2024)

Reduced synthesis of phospho-polysaccharide in Lactococcus as a strategy to evade phage infection - Conradus A.P. Giesbers; Jack Fagan; Elvina Parlindungan; Simon Palussière; Pascal Courtin; Gabriele A. Lugli; Marco Ventura; Saulius Kulakauskas; Marie-Pierre Chapot-Chartier; Jennifer Mahony; Douwe van Sinderen (International Journal of Food Microbiology, 2023)

Enzyme-immobilized hierarchically porous covalent organic framework biocomposite for catalytic degradation of broad-range emerging pollutants in water - Nada Elmerhi; Khadega Al-Maqdi; Khawlah Athamneh; Abdul Khayum Mohammed; Tina Skorjanc; Felipe Gándara; Jesus Raya; Simon Pascal; Olivier Siri; Ali Trabolsi; Iltaf Shah; Dinesh Shetty; et al. (Journal of Hazardous Materials, 2023)

Kinetics of metal and metalloid concentrations in holopelagic Sargassum reaching coastal environments - Océanne-Amaya Cipolloni; Magalie Baudrimont; Benoît Simon-Bouhet; Émilie Pauline Dassié; Julien Gigault; Solène Connan; Pierre-Yves Pascal (Environmental Science and Pollution Research, 2023)

The 2020–2021 seismic sequence in the Western Gulf of Corinth: Insights on the triggering mechanisms through high resolution seismological and geodetic data analysis - Anna Serpetsidaki; Vasilis Kapetanidis; Panagiotis Elias; Alexis Rigo; Ioannis Spingos; Louis De Barros; Olivier Lengliné; Simon Bufféral; Andreas Karakonstantis; Pascal Bernard; Pierre Briole; Jiří Zahradník; et al. (Tectonophysics, 2023)

Measuring landslide-driven ground displacements with high-resolution surface models and optical flow - Ellorine Carle; Pascal Sirguey; Simon C. Cox (Computers & Geosciences, 2023)

Endangered spined loach Cobitis species in Southwest Germany: A complex network of native, hybrid and newly emerged populations - Samuel Roch; Patrick Bartolin; Pascal Vonlanthen; Jan Baer; Simon Grundmüller; Laura S. Epp; Alexander Brinker (Fisheries Management and Ecology, 2023)
Successful conservation of cryptic species such as representatives of the genus Cobitis presents a challenge for fishery managers. Only Cobitis taenia L. is currently assumed to occur in southwest Germany, where it is classified as critically endangered. Established genetic markers and eDNA analysis identified three Cobitis species in the study area. Cobitis taenia and Cobitis elongatoides were widely distributed in the Rhine River system, primarily forming hybrid species complexes in which polyploid individuals dominate but coexist with diploid parent species. A third non‐native species, Cobitis bilineata , has recently become established in the southern part of the Rhine to which it probably migrated naturally via the connected Aare River system. In the Danube River catchment, two populations, including one previously thought to be extinct, comprise both diploid and polyploid representatives of C. elongatoides . Our results provide an important basis for more targeted conservation strategies for Cobitis species currently found in the region.

Monitoring erosion in tropical savannas from C-band radar coherence - Pascal Castellazzi; Sana Khan; Simon J. Walker; Rebecca Bartley; Scott N. Wilkinson; Jonathan C.L. Normand (Remote Sensing of Environment, 2023)

Substantial Organic and Particulate Nitrogen and Phosphorus Export from Geomorphologically Stable African Tropical Forest Landscapes - Simon Baumgartner; Marijn Bauters; Travis W. Drake; Matti Barthel; Serge Alebadwa; Nadine Bahizire; Basile Mujinya Bazirake; Johan Six; Pascal Boeckx; Kristof Van Oost (Ecosystems, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Sustain GEOBIM—a New Method to Simulate Sustainable Development Scenarios for Urban Areas - Heinz J. Bernegger; Patrick Laube; Pascal Ochsner; Mihaela Meslec; Hanno Rahn; Johann Junghardt; Isabella Aurich; Simon Ashworth (Circular Economy and Sustainability, 2021)
In 2015, 193 member states of the United Nations (UN) signed the 2030 Agenda, entitled “Transforming Our World: The 2030 Agenda for Sustainable Development,”. The planned implementation by 2030, leaves only a decade to realize the 17 Sustainable Development Goals (SDG). Municipalities and cities constitute important stakeholders, who are obliged under SDG 11, to find ways to develop realistic solutions. Implementation and strategic planning require, among other things, new instruments to digitally model various sustainable development scenarios. Currently, however, it is still unclear what has to be modelled and how. What is clear is that sustainability and digitalization have to come together to deliver results. Several key challenges need to be overcome. First, is the heterogeneity of existing data and documents used in the built environment. Future solutions will depend on a combination of Building Information Modelling (BIM) and Geographic Information System (GIS). Second, is the merging of different existing data on an adequate level of abstraction which allows practical use of GIS and BIM data in a common model. Third, is the development of functioning, cost-effective workflows that will enable broad applications which adequately simulate specific sustainability aspects using spatial and temporal scenarios. This paper shows how these challenges can be systematically addressed in practice. It demonstrates which aspects of sustainability can be made visible and comprehensible for all stakeholders using only one single BIM- and GIS based data model. The proposed workflow could thus be considered as the basis for planning the next generation of smart and sustainable cities.

Which Method for Which Purpose? A Comparison of Line Intercept Transect and Underwater Photogrammetry Methods for Coral Reef Surveys - Isabel Urbina-Barreto; Rémi Garnier; Simon Elise; Romain Pinel; Pascal Dumas; Vincent Mahamadaly; Mathilde Facon; Sophie Bureau; Christophe Peignon; Jean-Pascal Quod; Eric Dutrieux; Lucie Penin; et al. (Frontiers in Marine Science, 2021)
The choice of ecological monitoring methods and descriptors determines the effectiveness of a program designed to assess the state of coral reef ecosystems. Here, we comparer the relative performance of the traditional Line Intercept Transect (LIT) method with three methods derived from underwater photogrammetry: LIT on orthomosaics, photoquadrats from orthomosaics, and surface analyses on orthomosaics. The data were acquired at Reunion Island on five outer reef slopes and two coral communities on underwater lava-flows. Coral cover was estimated in situ using the LIT method and with LITs and photoquadrats digitized on orthomosaic. Surface analyses were done on the same orthomosaics. Structural complexity of the surveyed sites was calculated from digital elevation models using three physical descriptors (fractal dimension, slope, surface complexity), and used to explore their possible influence in coral cover estimates. We also compared the methods in terms of scientific outputs, the human expertise and time required. Coral cover estimates obtained with in situ LITs were higher than those obtained with digitized LITs and photoquadrats. Surfaces analyses on orthomosaics yielded the lowest but most the precise cover estimates (i.e., lowest sample dispersion). Sites with the highest coral cover also had the highest structural complexity. Finally, when we added scientific outputs, and requirements for human expertise and time to our comparisons between methods, we found that surface analysis on the orthomosaics was the most efficient method. Photoquadrats were more time-consuming than both in situ and digitized LITs, even though they provided coral cover estimates similar to those of digitized LITs and yielded more than one descriptor. The LIT in situ method remains the least time-consuming and most effective for species-level taxonomic identifications but is the most limited method in terms of data outputs and representativeness of the ecosystem.

Sediment source fingerprinting: benchmarking recent outputs, remaining challenges and emerging themes - Adrian L. Collins; Martin Blackwell; Pascal Boeckx; Charlotte-Anne Chivers; Monica Emelko; Olivier Evrard; Ian Foster; Allen Gellis; Hamid Gholami; Steve Granger; Paul Harris; Arthur J. Horowitz; et al. (Journal of Soils and Sediments, 2020)
Purpose This review of sediment source fingerprinting assesses the current state-of-the-art, remaining challenges and emerging themes. It combines inputs from international scientists either with track records in the approach or with expertise relevant to progressing the science. Methods Web of Science and Google Scholar were used to review published papers spanning the period 2013–2019, inclusive, to confirm publication trends in quantities of papers by study area country and the types of tracers used. The most recent (2018–2019, inclusive) papers were also benchmarked using a methodological decision-tree published in 2017. Scope Areas requiring further research and international consensus on methodological detail are reviewed, and these comprise spatial variability in tracers and corresponding sampling implications for end-members, temporal variability in tracers and sampling implications for end-members and target sediment, tracer conservation and knowledge-based pre-selection, the physico-chemical basis for source discrimination and dissemination of fingerprinting results to stakeholders. Emerging themes are also discussed: novel tracers, concentration-dependence for biomarkers, combining sediment fingerprinting and age-dating, applications to sediment-bound pollutants, incorporation of supportive spatial information to augment discrimination and modelling, aeolian sediment source fingerprinting, integration with process-based models and development of open-access software tools for data processing. Conclusions The popularity of sediment source fingerprinting continues on an upward trend globally, but with this growth comes issues surrounding lack of standardisation and procedural diversity. Nonetheless, the last 2 years have also evidenced growing uptake of critical requirements for robust applications and this review is intended to signpost investigators, both old and new, towards these benchmarks and remaining research challenges for, and emerging options for different applications of, the fingerprinting approach.

Evaluating the potential of full‐waveform lidar for mapping pan‐tropical tree species richness - Suzanne M. Marselis; Katharine Abernethy; Alfonso Alonso; John Armston; Timothy R. Baker; Jean‐Francois Bastin; Jan Bogaert; Doreen S. Boyd; Pascal Boeckx; David F. R. P. Burslem; Robin Chazdon; David B. Clark; et al. (Global Ecology and Biogeography, 2020)
Aim Mapping tree species richness across the tropics is of great interest for effective conservation and biodiversity management. In this study, we evaluated the potential of full‐waveform lidar data for mapping tree species richness across the tropics by relating measurements of vertical canopy structure, as a proxy for the occupation of vertical niche space, to tree species richness. Location Tropics. Time period Present. Major taxa studied Trees. Methods First, we evaluated the characteristics of vertical canopy structure across 15 study sites using (simulated) large‐footprint full‐waveform lidar data (22 m diameter) and related these findings to in‐situ tree species information. Then, we developed structure–richness models at the local (within 25–50 ha plots), regional (biogeographical regions) and pan‐tropical scale at three spatial resolutions (1.0, 0.25 and 0.0625 ha) using Poisson regression. Results The results showed a weak structure–richness relationship at the local scale. At the regional scale (within a biogeographical region) a stronger relationship between canopy structure and tree species richness across different tropical forest types was found, for example across Central Africa and in South America [ R 2 ranging from .44–.56, root mean squared difference as a percentage of the mean (RMSD%) ranging between 23–61%]. Modelling the relationship pan‐tropically, across four continents, 39% of the variation in tree species richness could be explained with canopy structure alone ( R 2 = .39 and RMSD% = 43%, 0.25‐ha resolution). Main conclusions Our results may serve as a basis for the future development of a set of structure–richness models to map high resolution tree species richness using vertical canopy structure information from the Global Ecosystem Dynamics Investigation (GEDI). The value of this effort would be enhanced by access to a larger set of field reference data for all tropical regions. Future research could also support the use of GEDI data in frameworks using environmental and spectral information for modelling tree species richness across the tropics.

Characterizing Exposure to and Sharing Knowledge of Drivers of Environmental Change in the St. Lawrence System in Canada - David Beauchesne; Rémi M. Daigle; Steve Vissault; Dominique Gravel; Andréane Bastien; Simon Bélanger; Pascal Bernatchez; Marjolaine Blais; Hugo Bourdages; Clément Chion; Peter S. Galbraith; Benjamin S. Halpern; et al. (Frontiers in Marine Science, 2020)

TIMP1 intron 3 retention is a marker of colon cancer progression controlled by hnRNPA1 - Marion Flodrops; Gwendal Dujardin; Adeline Busson; Pascal Trouvé; Chandran Ka; Brigitte Simon; Danielle Arzur; Catherine Le Jossic-Corcos; Laurent Corcos (Molecular Biology Reports, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

The protective role of liver X receptor (LXR) during fumonisin B1-induced hepatotoxicity - Marion Régnier; Arnaud Polizzi; Céline Lukowicz; Sarra Smati; Frédéric Lasserre; Yannick Lippi; Claire Naylies; Joelle Laffitte; Colette Bétoulières; Alexandra Montagner; Simon Ducheix; Pascal Gourbeyre; et al. (Archives of Toxicology, 2019)

Evaluation of the HadGEM3-A simulations in view of detection and attribution of human influence on extreme events in Europe - Robert Vautard; Nikolaos Christidis; Andrew Ciavarella; Carmen Alvarez-Castro; Omar Bellprat; Bo Christiansen; Ioana Colfescu; Tim Cowan; Francisco Doblas-Reyes; Jonathan Eden; Mathias Hauser; Gabriele Hegerl; et al. (Climate Dynamics, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Production of chlorzoxazone glucuronides via cytochrome P4502E1 dependent and independent pathways in human hepatocytes - Nicolas Quesnot; Simon Bucher; Christina Gade; Manuel Vlach; Elise Vene; Samuel Valença; Thomas Gicquel; Helle Holst; Marie-Anne Robin; Pascal Loyer (Archives of Toxicology, 2018)

Annual Phytoplankton Primary Production Estimation in a Temperate Estuary by Coupling PAM and Carbon Incorporation Methods - Jérôme Morelle; Mathilde Schapira; Francis Orvain; Philippe Riou; Pascal Jean Lopez; Olivier Pierre-Duplessix; Emilie Rabiller; Frank Maheux; Benjamin Simon; Pascal Claquin (Estuaries and Coasts, 2018)

Biosynthesis of abscisic acid in fungi: identification of a sesquiterpene cyclase as the key enzyme in Botrytis cinerea - Inmaculada Izquierdo‐Bueno; Victoria E. González‐Rodríguez; Adeline Simon; Bérengère Dalmais; Jean‐Marc Pradier; Pascal Le Pêcheur; Alex Mercier; Anne‐Sophie Walker; Carlos Garrido; Isidro González Collado; Muriel Viaud (Environmental Microbiology, 2018)
Summary While abscisic acid (ABA) is known as a hormone produced by plants through the carotenoid pathway, a small number of phytopathogenic fungi are also able to produce this sesquiterpene but they use a distinct pathway that starts with the cyclization of farnesyl diphosphate (FPP) into 2Z,4E‐α‐ionylideneethane which is then subjected to several oxidation steps. To identify the sesquiterpene cyclase (STC) responsible for the biosynthesis of ABA in fungi, we conducted a genomic approach in Botrytis cinerea . The genome of the ABA‐overproducing strain ATCC58025 was fully sequenced and five STC‐coding genes were identified. Among them, Bcstc5 exhibits an expression profile concomitant with ABA production. Gene inactivation, complementation and chemical analysis demonstrated that BcStc5/BcAba5 is the key enzyme responsible for the key step of ABA biosynthesis in fungi. Unlike what is observed for most of the fungal secondary metabolism genes, the key enzyme‐coding gene Bcstc5/Bcaba5 is not clustered with the other biosynthetic genes, i.e., Bcaba1 to Bcaba4 that are responsible for the oxidative transformation of 2Z,4E‐α‐ionylideneethane. Finally, our study revealed that the presence of the Bcaba genes among Botrytis species is rare and that the majority of them do not possess the ability to produce ABA.

A comparative review of fisheries management experiences in the E uropean U nion and in other countries worldwide: I celand, A ustralia, and N ew Z ealand - Paul Marchal; Jesper Levring Andersen; Martin Aranda; Mike Fitzpatrick; Leyre Goti; Olivier Guyader; Gunnar Haraldsson; Aaron Hatcher; Troels Jacob Hegland; Pascal Le Floc'h; Claire Macher; Loretta Malvarosa; et al. (Fish and Fisheries, 2016)
This study compares the details and performance of fisheries management between the EU and a selection of other countries worldwide: Iceland, New Zealand, and Australia, which are considered in many respects to be among the most advanced in the world in fisheries management. Fisheries management in the EU , Iceland, Australia, and New Zealand has developed following different paths, despite being based on similar instruments and principles. Iceland, Australia, and New Zealand have been at the forefront of developing management practices such as stakeholder involvement, legally binding management targets (Australia, New Zealand), individual transferable quotas, and discard bans (Iceland, New Zealand). The EU has since the beginning of the 21st century taken significant steps to better involve stakeholders and establish quantitative targets through management plans, and a landing obligation is gradually being implemented from 2015 onward. The management of domestic fisheries resources in Australia, New Zealand, and Iceland has, overall, performed better than in the EU , in terms of conservation and economic efficiency. It should, however, be stressed that, compared to Australia, New Zealand, and Iceland, (i) initial over‐capacity was more of an issue in the EU when management measures became legally binding and also that (ii) EU has been progressive in developing common enforcement standards, on stocks shared by sovereign nations. The situation of EU fisheries has substantially improved over the period 2004–2013 in the northeast Atlantic, with fishery status getting close to that in the other jurisdictions, but the lack of recovery for Mediterranean fish stocks remains a concern.

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Dissociable attentional and inhibitory networks of dorsal and ventral areas of the right inferior frontal cortex: a combined task-specific and coordinate-based meta-analytic fMRI study - Alexandra Sebastian; Patrick Jung; Jonathan Neuhoff; Michael Wibral; Peter T. Fox; Klaus Lieb; Pascal Fries; Simon B. Eickhoff; Oliver Tüscher; Arian Mobascher (Brain Structure and Function, 2016)

An integrated pan‐tropical biomass map using multiple reference datasets - Valerio Avitabile; Martin Herold; Gerard B. M. Heuvelink; Simon L. Lewis; Oliver L. Phillips; Gregory P. Asner; John Armston; Peter S. Ashton; Lindsay Banin; Nicolas Bayol; Nicholas J. Berry; Pascal Boeckx; et al. (Global Change Biology, 2016)
We combined two existing datasets of vegetation aboveground biomass ( AGB ) ( Proceedings of the National Academy of Sciences of the United States of America , 108 , 2011, 9899; Nature Climate Change , 2 , 2012, 182) into a pan‐tropical AGB map at 1‐km resolution using an independent reference dataset of field observations and locally calibrated high‐resolution biomass maps, harmonized and upscaled to 14 477 1‐km AGB estimates. Our data fusion approach uses bias removal and weighted linear averaging that incorporates and spatializes the biomass patterns indicated by the reference data. The method was applied independently in areas (strata) with homogeneous error patterns of the input (Saatchi and Baccini) maps, which were estimated from the reference data and additional covariates. Based on the fused map, we estimated AGB stock for the tropics (23.4 N–23.4 S) of 375 Pg dry mass, 9–18% lower than the Saatchi and Baccini estimates. The fused map also showed differing spatial patterns of AGB over large areas, with higher AGB density in the dense forest areas in the Congo basin, Eastern Amazon and South‐East Asia, and lower values in Central America and in most dry vegetation areas of Africa than either of the input maps. The validation exercise, based on 2118 estimates from the reference dataset not used in the fusion process, showed that the fused map had a RMSE 15–21% lower than that of the input maps and, most importantly, nearly unbiased estimates (mean bias 5 Mg dry mass ha −1 vs. 21 and 28 Mg ha −1 for the input maps). The fusion method can be applied at any scale including the policy‐relevant national level, where it can provide improved biomass estimates by integrating existing regional biomass maps as input maps and additional, country‐specific reference datasets.

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Evaluating the genetic effects of the invasive O cenebra inornata on the native oyster drill O cenebra erinacea - Eric Pante; Pierre‐Yves Pascal; Vanessa Becquet; Amélia Viricel; Benoit Simon‐Bouhet; Pascale Garcia (Marine Ecology, 2015)
Studies focusing on the effect of invasive species on the genetic diversity of native marine invertebrates remain scant. Here we report diversity among French populations of the intertidal gastropod Ocenebra erinacea (Linnaeus, 1758) sampled in the presence and absence of the invasive Ocenebra inornata (Recluz, 1851). Between 1999 and 2004, a total of 352 individuals of O. erinacea was collected from 15 sites (five of which had the invasive present) and was genotyped at the mitochondrial locus Cytochrome Oxidase 1 ( cox1 ). No statistical difference was observed between polymorphism levels recorded within native populations exposed to the invasive, compared with populations sampled in the absence of O . inornata . No sign of native population decline was detected in response to the invader. While significant shifts in native O . erinacea population sizes have previously been reported in the literature, genetic effects may take longer to accumulate, or may be undetectable without a larger panel of genetic markers. By contrast, large genetic distances and significant population differentiation were recorded between Atlantic and Mediterranean O . erinacea samples, suggesting that these populations have distinct evolutionary histories. Comparison of genetic divergence within the closely related genus Nucella suggests that the Atlantic populations of O . erinacea and those from Thau Lagoon in the Mediterranean may belong to different species or subspecies.

Focal adhesion kinase (FAK) perspectives in mechanobiology: implications for cell behaviour - Pascal Tomakidi; Simon Schulz; Susanne Proksch; Wilfried Weber; Thorsten Steinberg (Cell and Tissue Research, 2014)

A harbour–canal at Portus: a geoarchaeological approach to the Canale Romano: Tiber delta, Italy - Ferréol Salomon; Jean-Philippe Goiran; Jean-Paul Bravard; Pascal Arnaud; Hatem Djerbi; Stephen Kay; Simon Keay (Water History, 2014)

Impact of climate change on the hydrogeology of two basins in northern France - Florence Habets; Julien Boé; Michel Déqué; Agnès Ducharne; Simon Gascoin; Ali Hachour; Eric Martin; Christian Pagé; Eric Sauquet; Laurent Terray; Dominique Thiéry; Ludovic Oudin; et al. (Climatic Change, 2013)

Divergent evolutionary processes associated with colonization of offshore islands - Natália Martínková; Ross Barnett; Thomas Cucchi; Rahel Struchen; Marine Pascal; Michel Pascal; Martin C. Fischer; Thomas Higham; Selina Brace; Simon Y. W. Ho; Jean‐Pierre Quéré; Paul O'Higgins; et al. (Molecular Ecology, 2013)
Oceanic islands have been a test ground for evolutionary theory, but here, we focus on the possibilities for evolutionary study created by offshore islands. These can be colonized through various means and by a wide range of species, including those with low dispersal capabilities. We use morphology, modern and ancient sequences of cytochrome b ( cytb ) and microsatellite genotypes to examine colonization history and evolutionary change associated with occupation of the O rkney archipelago by the common vole ( M icrotus arvalis ), a species found in continental E urope but not in B ritain. Among possible colonization scenarios, our results are most consistent with human introduction at least 5100 bp (confirmed by radiocarbon dating). We used approximate B ayesian computation of population history to infer the coast of Belgium as the possible source and estimated the evolutionary timescale using a Bayesian coalescent approach. We showed substantial morphological divergence of the island populations, including a size increase presumably driven by selection and reduced microsatellite variation likely reflecting founder events and genetic drift. More surprisingly, our results suggest that a recent and widespread cytb replacement event in the continental source area purged cytb variation there, whereas the ancestral diversity is largely retained in the colonized islands as a genetic ‘ark’. The replacement event in the continental M . arvalis was probably triggered by anthropogenic causes (land‐use change). Our studies illustrate that small offshore islands can act as field laboratories for studying various evolutionary processes over relatively short timescales, informing about the mainland source area as well as the island.

Neophobia and social tolerance are related to breeding group size in a semi-colonial bird - Sophie Dardenne; Simon Ducatez; Julien Cote; Pascal Poncin; Virginie M. Stevens (Behavioral Ecology and Sociobiology, 2013)

Liver damage and systemic inflammatory responses are exacerbated by the genetic deletion of CD39 in total hepatic ischemia - Xiaofeng Sun; Masato Imai; Martina Nowak-Machen; Olaf Guckelberger; Keiichi Enjyoji; Yan Wu; Zain Khalpey; Pascal Berberat; Jeeva Munasinghe; Simon Christopher Robson (Purinergic Signalling, 2011)

Polymorphic variants in tenascin-C (TNC) are associated with atherosclerosis and coronary artery disease - Mollie A. Minear; David R. Crosslin; Beth S. Sutton; Jessica J. Connelly; Sarah C. Nelson; Shera Gadson-Watson; Tianyuan Wang; David Seo; Jeffrey M. Vance; Michael H. Sketch; Carol Haynes; Pascal J. Goldschmidt-Clermont; et al. (Human Genetics, 2011)

Improved Constraints on Models of Glacial Isostatic Adjustment: A Review of the Contribution of Ground-Based Geodetic Observations - Matt A. King; Zuheir Altamimi; Johannes Boehm; Machiel Bos; Rolf Dach; Pedro Elosegui; François Fund; Manuel Hernández-Pajares; David Lavallee; Paulo Jorge Mendes Cerveira; Nigel Penna; Riccardo E. M. Riva; et al. (Surveys in Geophysics, 2010)

Optimisation of contained Nicotiana tabacum cultivation for the production of recombinant protein pharmaceuticals - Richard Colgan; Christopher J. Atkinson; Matthew Paul; Sally Hassan; Pascal M. W. Drake; Amy L. Sexton; Simon Santa-Cruz; David James; Keith Hamp; Colin Gutteridge; Julian K-C. Ma (Transgenic Research, 2010)

Genetic effects in the leukotriene biosynthesis pathway and association with atherosclerosis - David R. Crosslin; Svati H. Shah; Sarah C. Nelson; Carol S. Haynes; Jessica J. Connelly; Shera Gadson; Pascal J. Goldschmidt-Clermont; Jeffery M. Vance; Jason Rose; Chris B. Granger; David Seo; Simon G. Gregory; et al. (Human Genetics, 2009)

Peripherally Presented Emotional Scenes: A Spatiotemporal Analysis of Early ERP Responses - Simon Rigoulot; Sylvain Delplanque; Pascal Despretz; Sabine Defoort-Dhellemmes; Jacques Honoré; Henrique Sequeira (Brain Topography, 2008)

Error Analysis of Weekly Station Coordinates in the DORIS Network - Simon D. P. Williams; Pascal Willis (Journal of Geodesy, 2006)

Expressed sequence tags from the phytopathogenic fungus Botrytis cinerea - Muriel Viaud; Fabrice Legeai; Jean-Marc Pradier; Yves Brygoo; Frdrique Bitton; Jean Weissenbach; Adeline Brunet-Simon; Aymeric Duclert; Sabine Fillinger; Dominique Fortini; Anastasia Gioti; Corinne Giraud; et al. (European Journal of Plant Pathology, 2005)

A QTL with major effect on milk yield and composition maps to bovine Chromosome 14 - Wouter Coppieters; Juliette Riquet; Juan-José Arranz; Paulette Berzi; Nadine Cambisano; Bernard Grisart; Latifa Karim; Fabienne Marcq; Laurence Moreau; Carine Nezer; Patricia Simon; Pascal Vanmanshoven; et al. (Mammalian Genome, 1998)

Biological components from the Seine estuary: first results - Pascal Mouny; Jean Claude Dauvin; Christophe Bessineton; Bernard Elkaim; Serge Simon (Hydrobiologia, 1998)